The Listener and the Work as the Dualistic Basis for the Morphological Analysis of Music - Glivinsky, Valery (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
In morphological analysis, the musical work and the listener are seen as elements of one communicative duality. Each element of this duality may play the role of either subject or object. Morphological analysis takes sound construction as its main target. This makes possible a more flexible approach to analyzing a musical text. The morpheme, one of the cornerstones of morphological analysis, can be defined as a sound construction with a typical set of characteristic features. The other cornerstone, the morph, transforms a morpheme into a genеriс, stylistic “flesh and blood” of a specific musical text, on the basis of polymorphism. From the point of view of morphological analysis, the musical development in the “Introduction” to Stravinsky’s The Rite of Spring is based on a step-by-step approach to an externally existing object, permitting us to perceive (see or hear) its details. The object itself is polymorphic, i.e., like an embryo, it contains within itself, from the start, every element it needs for further development. The starting point of the “Introduction,” the high-register bassoon melody accompanied by the supporting French horn voice, can be defined as a forest seen in a distance, from where the sound of a shepherd’s horn can be heard. The ten intonational elements of the initial three measures of the ballet are the base from which the form of the “Introduction” is developed.